Perspektif Hukum Ekonomi Syariah Terhadap Instrumen Pasar Modal Syariah diIndonesia (Investasi Pada Obligasi Syariah (Sukuk) Dan Saham Syariah) - Nurul Kharisma; Faiza Nadilah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted with the aim of knowing how the law of invesment in Islamic capital market instruments, especially in Islamic bonds and Islamic stocks, when viewed from the perspective of Islamic economic law. This research uses qualitative research methods with literature review. Based on the research, it is found that investing in Islamic capital market instruments, namely Islamic bonds and Islamic stocks, is allowed. This is seen from previous research and is supported by the existence of the DSN-MUI Fatwa which discusses the Islamic capital market. In addition, the research results are also strengthened by the existence of arguments that allow investment in both Islamic capital market instruments.